STRATEGIC DIGITAL MARKETING FOR MICRO, SMALL, MEDIUM ENTERPRISES (MSME): ENHANCING COMMUNITY ENGAGEMENT AND ECONOMIC EMPOWERMENT IN ISLAMIC SOCIETIES - Suryani, Nani; Nurhayati, Sri; Rakhman, Anita; Boriboon, Gumpanat (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2024)
The research examines using digital platforms such as Instagram, TikTok, and WhatsApp to drive business growth, enhance community engagement, and promote economic empowerment while strictly adhering to Islamic ethical principles. Employing a qualitative case study methodology in Salon Jois Bandung, including in-depth interviews, direct observations, and document analysis, the findings reveal that aligning digital marketing strategies with cultural and religious values is pivotal for fostering customer acquisition, retention, and loyalty. The research highlights the critical role of ethical considerations in shaping digital marketing practices in culturally sensitive contexts, such as those found in Islamic societies. The case of Salon Jois demonstrates that MSMEs can effectively leverage digital platforms to build robust community connections and achieve sustainable growth, provided they carefully navigate the ethical complexities inherent in these markets. This research contributes to the existing literature on digital marketing in Islamic contexts by offering practical insights into culturally sensitive marketing practices and emphasizing the potential of digital marketing to advance the broader objectives of Islamic community development. The findings advocate for further scholarly inquiry into integrating contemporary marketing tools with traditional Islamic values, which is crucial for the sustainable development of MSMEs in Muslim-majority regions.